호흡수련체조가 1기 고혈압 중년여성의 혈압, 혈중지질 및 스트레스 변화에 미치는 영향 - 김은정; 김지선 (Exercise science (Seoul, Korea), 2014)
본 연구는 호흡수련체조가 1기 고혈압 중년여성의 혈압, 혈중지질 및 스트레스 변화에 미치는 영향을 규명하고자 한다. 피험자는 40-50대 중년여성 30명을 대상으로 실험집단 15명, 통제집단 15명을 무선 할당하여 호흡수련체조를 12주간 주 5회, 1일 60분씩 실시하였다. 이를 통해 얻어진 결론은 다음과 같다. 첫째, 수축기혈압, 이완기혈압, TG, HDL-C, LDL-C는 집단과 시기의 주효과와 상호작용효과 모두 유의미한 차이를 보였고, TC는 집단과 시기의 주효과, 상호작용효과 모두 통계적으로 유의미한 차이를 보이지 않았다. 둘째, 사회적 역할수행 및 자기 신뢰요인, 수면장애 및 불안요인, 전체 스트레스는 집단과 시기의 주효과와 상호작용효과 모두 유의미한 차이를 보였다. 이상의 결과로 호흡수련체조는 1기 고혈압 중년여성의 혈압 강하와 혈중지질 개선 및 스트레스 감소에 효과적인 영향을 미치는 심신수련 운동중재의 효과를 기대 할 수 있다고 사료되어진다. The purpose of this study was to closely examine the influence of breathing training gymnastics on a change in blood pressure, blood lipid, and stress of middle-aged women with stage 1 hypertension. Subjects were randomly allocated 15 people to experimental group and 15 people to control group targeting 30 of 40-50 middle-aged women. Breathing training gymnastics was carried out 60 minutes a day, 5 times a week for 12 weeks. The followings are the conclusions that were obtained in this study. First, systolic blood pressure, diastolic blood pressure, TG, HDL-C, LDL-C showed significant difference in both main effect and interaction effect of group and period. TC didn't show statistically significant difference in both main effect and interaction effect of group and period. Second, social role performance & self-reliance factor, sleep disorder & anxiety factor, and whole stress showed significant difference in both main effect and interaction effect of group and period. As a result of the above, the breathing training gymnastics is considered to be possibly expected the impact of mind-body training exercise intervention, which has effective influence upon a fall in blood pressure, improvement in blood lipid, and reduction in stress of the middle-aged women with stage 1 hypertension. KCI Citation Count: 7